A Mathematical Model of Myosin Heavy Chain Dynamics in the Disintegration of Golden Threadfin Bream Nemipterus virgatus Surimi Gel - Ryoko Nakamizo; Tatsuya Hayashi; Yuri Kominami; Hideki Ushio (Gels)
Surimi gel, a type of hydrocolloidal food, is formed through the gelation of fish meat proteins. Myosin heavy chain (MHC), a key myofibrillar protein, plays a crucial role in the formation of the gel network via both transglutaminase (TGase)-catalyzed and non-enzymatic polymerization. Gel disintegration in surimi is primarily attributed to the proteolytic degradation of MHC. This study focused on golden threadfin bream Nemipterus virgatus, a species characterized by low TGase activity and high protease activity at elevated temperatures. We investigated the competition between non-enzymatic polymerization and proteolytic degradation of MHC and their effects on gel mechanical properties using a mathematical model. A mathematical model based on kinetic reactions accurately reflected the changes in MHC observed through SDS-PAGE analysis during N. virgatus gel disintegration. Our results indicate that not only unpolymerized but also polymerized MHC was significantly degraded, which substantially contributed to the reduction in the mechanical properties of the N. virgatus surimi. Mathematically understanding the dynamics of MHC in surimi during heating helps promote the utilization of noncommercial fish species for surimi processing by enabling better control over surimi gel properties.